The in vitro and in vivo effects of constitutive light expression on a bioluminescent strain of the mouse enteropathogen Citrobacter rodentium - Read, Hannah M. (PeerJ, 2016)
Bioluminescent reporter genes, such as those from fireflies and bacteria, let researchers use light production as a non-invasive and non-destructive surrogate measure of microbial numbers in a wide variety of environments. As bioluminescence needs microbial metabolites, tagging microorganisms with luciferases means only live metabolically active cells are detected. Despite the wide use of bioluminescent reporter genes, very little is known about the impact of continuous (also called constitutive) light expression on tagged bacteria. We have previously made a bioluminescent strain of Citrobacter rodentium, a bacterium which infects laboratory mice in a similar way to how enteropathogenic Escherichia coli (EPEC) and enterohaemorrhagic E. coli (EHEC) infect humans. In this study, we compared the growth of the bioluminescent C. rodentium strain ICC180 with its non-bioluminescent parent (strain ICC169) in a wide variety of environments. To understand more about the metabolic burden of expressing light, we also compared the growth profiles of the two strains under approximately 2,000 different conditions. We found that constitutive light expression in ICC180 was near-neutral in almost every non-toxic environment tested. However, we also found that the non-bioluminescent parent strain has a competitive advantage over ICC180 during infection of adult mice, although this was not enough for ICC180 to be completely outcompeted. In conclusion, our data suggest that constitutive light expression is not metabolically costly to C. rodentium and supports the view that bioluminescent versions of microbes can be used as a substitute for their non-bioluminescent parents to study bacterial behaviour in a wide variety of environments.